1998
DOI: 10.1577/1548-8659(1998)127<0275:trpomj>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity Reduces Predation on Migrating Juvenile Pacific Salmon

Abstract: We field tested the hypothesis that predation by piscivorous fish is reduced in turbid compared with clear water. The Harrison River (Յ1 nephelometric turbidity units, NTU) is a clear tributary of the naturally turbid Fraser River (27-108 NTU), in British Columbia, Canada. Age-0 juveniles of Harrison River stocks of Pacific salmon Oncorhynchus spp. migrating seaward in spring obligately pass through turbid and clear reaches of these rivers. To test the hypothesis, we compared predation on salmonids by potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 32 publications
(56 reference statements)
6
134
1
Order By: Relevance
“…The relationship describing the abundance of Epeorus as a response to turbidity and conductivity by the best-fit regression model shows an expected pattern of decreased abundance with increasing values for both predictors, following the previous identification as an indicator of ideal habitat and low tolerance (Merritt et al 2008). This and other studies in rivers in this region of the Pacific Northwest have shown a relationship between decreased water quality and increases in turbidity and conductivity, with resultant impacts on the endemic biota, specifically decreases in macroinvertebrate richness (Gregory and Levings 1998).…”
Section: Discussionsupporting
confidence: 65%
“…The relationship describing the abundance of Epeorus as a response to turbidity and conductivity by the best-fit regression model shows an expected pattern of decreased abundance with increasing values for both predictors, following the previous identification as an indicator of ideal habitat and low tolerance (Merritt et al 2008). This and other studies in rivers in this region of the Pacific Northwest have shown a relationship between decreased water quality and increases in turbidity and conductivity, with resultant impacts on the endemic biota, specifically decreases in macroinvertebrate richness (Gregory and Levings 1998).…”
Section: Discussionsupporting
confidence: 65%
“…Fish reared in turbid water were generally more active than fish reared in clear water during the predation trial. This may represent a decrease in perceived risk for turbid developmental treatment guppies, since turbidity may offer a refuge from predators that rely on sight (Gregory and Levings 1998;Lehtiniemi et al 2005). If turbid developmental treatment guppies are safer in turbid water when predators are present due to decreased abilities for predators to detect prey, they may doubly benefit by having increased motion detection abilities (due to increase in LWS opsin expression) compared to fish reared in clear water.…”
Section: Anti-predator Behavior In Turbid Watermentioning
confidence: 99%
“…While we have shown that turbidity affects a common prey species in Trinidadian streams, future studies should incorporate effects of turbidity on major predators if we are to understand how turbidity affects predator-prey interactions. Increasing turbidity may decrease predation if predators are less able to locate prey under cover of turbidity (Miner and Stein 1996;Abrahams and Kattenfeld 1997;Gregory and Levings 1998). Conversely, asymmetries in the abilities of predators and prey to detect one another (Wenger et al 2013), or constraints on prey recognition of predators and learning in turbid water (Ferrari et al 2010) may result in greater predation.…”
Section: Anti-predator Behavior In Turbid Watermentioning
confidence: 99%
“…As errors may be exacerbated by environmental conditions [19], we explore the impact of increasing environmental turbidity on the selfish herd responses of our guppy shoals. In aquatic systems, increasing turbidity degrades the visual environment, shortening response distances to conspecifics [24,25], predators [26,27] and prey [28][29][30] in many species including guppies [24,25]. We predict that increasing turbidity will result in either (i) a switch from more complex to simpler rules as fewer shoalmates can be detected or (ii) increased error in evaluation of the position of shoalmates, leading to increased error in following any rule.…”
Section: Introductionmentioning
confidence: 99%